Fatigue behaviour of latex modified reinforced concrete beams - Prasad, Brajkishor (Journal of Structural Engineering, 2024)
The slow cyclic fatigue behaviour under flexural loading of Latex Modified Reinforced Concrete (LMRC) beams containing 10 and 15 percent latex made of M30 grade has been investigated. The beams were tested in such a manner that in some cases the maximum load level was kept below the permissible load level (peak of stability point as obtained under cyclic tests) to confirm the permissible load level while in other cases the maximum load level was kept above the permissible load such that the accumulation of strains to failure occur due to the repetition of load cycles. The envelope curve, stability point curve and load capacity of LMRC beams obtained from load-deflection plots under flexural fatigue tests were compared with that of cyclic tests. The results obtained are in close proximity with that observed under cyclic tests.